LAY FORUMS IN CHILD WELFARE - Schmid, Jeanette (Social Work/Maatskaplike Werk, 2007)
Dealing with child abuse presents many challenges to both policy makers and service providers internationally. Societies have responded differently to this issue (Gough, 1996). In Western countries two broad streams have emerged: one adversarial, the other consensual. The “child protection” approach, common in countries such as the UK, USA, Canada and Australia, has been criticised as being punitive and adversarial, typically marginalising the voice and experience of service users (Merkel-Holguin, 2004; Waldegrave, 2006; Waldfogel, 1998). A more collaborative approach to child welfare is captured in the “family services” and “community care” models, respectively typical of Europe and of aboriginal communities in “developed” countries. It should be noted that the limited literature on child welfare systems operating in “developing” countries implies that services mostly conform to a “child protection” approach as they tend to be residual, deficit based and treatment oriented, and are heavily skewed towards residential care options (Pilotti, 1999; Stockholm University, 2003; Xiaoyuan & Xioaming, 2003). Indigenous helping approaches co-existing with these systems have typically been overlooked. The “community care” model hence constitutes the only child welfare model that formally articulates indigenous approaches.